Electrical properties of bromine doped SnSe2 van der Waals material. (9th October 2018) - Hyeon, Da Seul; Oh, Min Suk; Kim, Jin Tae; Lee, Yong Jei; Kim, Sang-il; Moon, Seung Pil; Hamayoun, Nadra; Kim, Sung Wng; Lee, Kyu Hyoung; Bang, Joonho; Lee, Kimoon
Abstract: Electrical properties of Br-doped SnSe2 van der Waals (vdW) materials are investigated by synthesizing polycrystalline SnSe2− x Br x via a solid-state reaction route. From the x-ray diffraction and Raman spectra results, it can be confirmed that Br impurity substitutes well on a Se-site by minimizing the lattice deformation as well as the red-shift of A 1g vibrational mode corresponding to the Sn–Se bond. Electrical characterization reveals that Br dopant is an efficient electron donor for vdW SnSe2 system as it easily encourages the electron carrier concentration from ~10 17 to ~10 20 cm −3, thus resulting in the semiconductor-metal transition behavior.